Corrosion and mechanical performance of double-layered nano-Al/PCL coating on Mg-Ca-Bi alloy - Bakhsheshi-Rad, Hamid Reza (Elsevier Ltd., 2015)
To improve corrosion resistance and reduce mechanical properties loss of Mg-Ca-Bi alloy, nano-aluminium (Al) and poly(e-caprolactone) (PCL) were prepared on a substrate of this alloy through physical vapour deposition (PVD) and dip coating techniques. The coating is composed of a thick outer interconnected pores PCL layer and a thin inner dense Al layer. The results showed that the compressive strength of nano-Al/PCL after immersion in NaCL solution is significantly higher than nano-Al coated samples but nano-Al showed better bonding strength of 25.6 MPa than that of nano-Al/PCL which was 8.1 MPa only. The results of electrochemical tests indicated that the bi-layered nano-Al/PCL coating dramatically increased the corrosion resistance of the Mg-Ca-Bi alloy.